ANALISIS MANAJEMEN RISIKO PADA UMKM MEGA DURIAN - Tarigan, Paulus; Nduru, Sesilia (Yayasan Sagita Akademia Maju, 2024)
Micro, Small and Medium Enterprise are the foundation of the Indonesian economy and are classified as such. Therefore, several government and regional programs are needed to implement better development of small and medium businesses, so that they can produce quality regional products. For example, the case study studied states that the problems often faced by Micro, Small and Medium Enterprise are lack of capital, lack of marketing such as promotional media and lack of packaging, as well as a lack of human resources which have an impact on production volume and product quality. The purpose of this research was to find out how big the impact of HR’s influence is on an ongoing business or business, and which risk management is suitable to be implemented in Micro, Small and Medium Enterprise businesses. This research uses a qualitative method. Based on the results of observations and interviews conducted with business owners, risk identification at Mega Durian is focused on operational risk because problems tend to often arise from business operations. Therefore, to avoid violations in the Mega Durian business, Risk Management is needed.